Sequence based typing for BoLA-DQA1 alleles in Indian zebu and its crossbred populations - VANDRE, R K; SHARMA, A K; GOWANE, G R; SANKAR, M; SANYAL, A; PATTNAIK, B (The Indian Journal of Animal Sciences, 2016)
Polymorphism in the major histocompatibility complex of the bovine, which is referred to as bovine leukocyte antigens (BoLAs), was intensively investigated for identifying marker(s) for bovine diseases and immunological traits. This approach requires identifying and documenting the allelic diversity of BoLA among different breeds of cattle using PCR-SBT technique. In this study, we could standardise the most useful approach of unravelling polymorphism in DQA1 exon 2 of cattle using PCR-sequence based typing (SBT). We could identify 16 different DQA1 alleles in 43 zebu and crossbred cattle, out of which 26 were homozygous and 17 were heterozygous. PCR- SBT has proved to be the most useful method for exploring the allelic polymorphism in DQA1 gene in zebu and its crossbred cattle in our study. Further use of this technique is equally appropriate for all kinds of traits i.e. production, reproduction and growth type of traits and beneficial for establishing new breeding objectives.